2022
DOI: 10.1038/s43016-022-00648-y
|View full text |Cite|
|
Sign up to set email alerts
|

Climate-friendly and nutrition-sensitive interventions can close the global dietary nutrient gap while reducing GHG emissions

Abstract: Under domestic-production-based scenarios, the nutrient gap is closed via changes to domestic production of food sources that minimize the emissions based on national production baskets. No change in nutrient adequacy is imposed for countries with adequate nutrient supply (for more details, see Scenario description). In contrast, under the trade scenario, the nutrient gap is closed via imports of optimal food sources from optimal trade partners that minimize the emissions based on current import baskets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In the field of food security, certain studies investigated the effects of country interactions within the global food system on social, political, economic, or environmental dimensions at national or regional levels ( Ericksen, 2008 ; Lagi et al, 2012 ; Shutters and Muneepeerakul, 2012 ; Sartori and Schiavo, 2015 ; García, 2019 ; Geyik et al, 2023 ), including analysis of sustainability and interdependence of countries on natural resources for food production ( D'Odorico et al, 2014 ; Khoury et al, 2015 ).…”
Section: Theorymentioning
confidence: 99%
“…In the field of food security, certain studies investigated the effects of country interactions within the global food system on social, political, economic, or environmental dimensions at national or regional levels ( Ericksen, 2008 ; Lagi et al, 2012 ; Shutters and Muneepeerakul, 2012 ; Sartori and Schiavo, 2015 ; García, 2019 ; Geyik et al, 2023 ), including analysis of sustainability and interdependence of countries on natural resources for food production ( D'Odorico et al, 2014 ; Khoury et al, 2015 ).…”
Section: Theorymentioning
confidence: 99%
“…Studies have shown that adopting a healthier diet in developed countries can curb food demand while promoting environmental sustainability 11 . However, achieving healthy and sustainable diets in low-income countries, particularly in Africa, may require signi cantly higher food consumption 12 . This, in turn, can increase water use 8 and GHG emissions 10 and decreasing affordability 13 as a major barrier to dietary transitions in developing countries.…”
Section: Mainmentioning
confidence: 99%
“…Agriculture is a significant contributor to global greenhouse gas (GHG) emissions and the major cause of land use change and freshwater use (Clark et al., 2019). It follows that the environmental impact of the food supply sector must be carefully managed (Jägermeyr et al., 2021; Soria‐Lopez et al., 2023; Springmann et al., 2018), especially because more food is needed to accommodate the increasing global population (Gerten et al., 2020) and improve nutrition (Eastham and Creedon, 2023; Geyik et al., 2023; Stylianou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%